The Emotional Design of Street Furniture Based on Kano Modeling - Zhaoxing Wang; Chao Han; Bing Yu; Kexin Wei; Yiqing Li; Sanfeng Jin; Panpan Bai (Buildings)
With the acceleration of urbanization, the design of street furniture, as an indispensable part of urban public spaces, faces the challenge of neglecting the user experience. To address this situation, this study adopted a three-level theory of affective design and the Kano model to categorize and rank users’ affective needs. The results show that users prefer high-density street furniture that follows traditional urban space design and incorporates elements of traditional Chinese culture and they reject minimalist modern facilities and empty, “hard” plazas. Accordingly, this study proposes emotional design strategies to effectively address the existing problems. Furthermore, this study confirms that the Kano model has significant advantages in identifying the real emotional needs of users, providing data support, and guiding the emotional design of street furniture, which ensures the scientific validity and effectiveness of the design strategy. This study not only deepens the understanding of the emotional design of street facilities but also provides an important reference for future urban space design and planning.